2009
DOI: 10.1080/15287390903213095
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Low-Level Cadmium and Arsenic on the Kidney

Abstract: Cadmium (Cd) and arsenic (As) are widely distributed in the environment and are known human carcinogens. Several studies reported that chronic exposure to Cd and As produced renal injuries in humans. As one of the mechanisms, oxidative stress was suggested to play a role in the early process of Cd- and/or As-induced tubular damage in the kidney. This study was performed to evaluate the significance of urinary biomarkers, role of oxidative stress, and effect of coexposure to environmental low-level exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…25 It has been monitored in some studies that As increased activities of the oxidant enzymes such as heme oxygenase-1, cyclooxygenase-2 and NADPH that were considered to responsible for the production of arsenic. [30][31][32] ROS leads to oxidation of macromolecules, mainly cell membrane lipids, proteins and DNA. The oxidation of lipids in the cell membrane causes changes in the membrane characteristics and starts a process that leads up to complete loss of the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 It has been monitored in some studies that As increased activities of the oxidant enzymes such as heme oxygenase-1, cyclooxygenase-2 and NADPH that were considered to responsible for the production of arsenic. [30][31][32] ROS leads to oxidation of macromolecules, mainly cell membrane lipids, proteins and DNA. The oxidation of lipids in the cell membrane causes changes in the membrane characteristics and starts a process that leads up to complete loss of the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Messarah et al 31 have reported that arsenic causes increased level of TBARS, being used in the evaluation of lipid peroxidation, in renal tissue. Huang et al 32 have conducted a study with 290 adults who were exposed to arsenic and reported that levels of MDA and 8-hydroxy-2 0 -deoxyguanosine, used as an indicator of DNA damage, and that urine arsenic level was positively correlated with these indicators. However, there are also studies that have reported that arsenic does not lead to an elevation in the level of lipid peroxidation in renal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced from Nordberg et al (2005), with permission from the publisher. endpoints (Huang et al, 2009) also show that coexposure to these elements produced more pronounced effects than with either element alone.…”
Section: Joint Action Of Cadmium and Other Metalsmentioning
confidence: 93%
“…Kidney is the key organ to eliminate heavy metals from the body. Heavy metals might lead to albuminuria through inducing oxidative stress to renal tubular cells (118,119). Certain heavy metals have additive effect in inducing nephrotoxicity.…”
Section: Heavy Metals and Environmental Pollutantsmentioning
confidence: 99%
“…For example, synergistic effect of arsenic (As) and cadmium (Cd) in causing renal damage has been demonstrated in Chinese general population (120). In addition, chronic exposure to toxic heavy metals may promote atherosclerosis and contribute to the development of chronic kidney disease and cardiovascular diseases (119,121). Furthermore, air pollutants can provoke systemic proinflammatory and pro-thrombotic response and lead to increase in platelet counts and platelet activation (122).…”
Section: Heavy Metals and Environmental Pollutantsmentioning
confidence: 99%